High-risk human papillomavirus viral load and persistence among heterosexual HIV-negative and HIV-positive men. (30th January 2014) - Grabowski, Mary K; Gray, Ronald H; Serwadda, David; Kigozi, Godfrey; Gravitt, Patti E; Nalugoda, Fred; Reynolds, Steven J; Wawer, Maria J; Watya, Stephen; Quinn, Thomas C; Tobian, Aaron A R
Abstract : Objectives: High-risk human papillomavirus (HR-HPV) viral load is associated with HR-HPV transmission and HR-HPV persistence in women. It is unknown whether HR-HPV viral load is associated with persistence in HIV-negative or HIV-positive men. Methods: HR-HPV viral load and persistence were evaluated among 703 HIV-negative and 233 HIV-positive heterosexual men who participated in a male circumcision trial in Rakai, Uganda. Penile swabs were tested at baseline and 6, 12 and 24 months for HR-HPV using the Roche HPV Linear Array, which provides a semiquantitative measure of HPV shedding by hybridisation band intensity (graded: 1–4). Prevalence risk ratios (PRR) were used to estimate the association between HR-HPV viral load and persistent detection of HR-HPV. Results: HR-HPV genotypes with high viral load (grade:3–4) at baseline were more likely to persist than HR-HPV genotypes with low viral load (grade: 1–2) among HIV-negative men (month 6: adjPRR=1.83, 95% CI 1.32 to 2.52; month 12: adjPRR=2.01, 95% CI 1.42 to 3.11), and HIV-positive men (month 6: adjPRR=1.33, 95% CI 1.06 to 1.67; month 12: adjPRR=1.73, 95% CI 1.18 to 2.54). Long-term persistence of HR-HPV was more frequent among HIV-positive men compared with HIV-negative men (month 24: adjPRR=2.27, 95% CI 1.47 to 3.51). Persistence of newly detected HR-HPV at the 6-month and 12-month visits with high viral load were also more likely to persist to 24 months than HR-HPV with low viral load among HIV-negative men (adjPRR=1.67, 95% CI 0.88 to 3.16). Conclusions: HR-HPV genotypes with high viral load are more likely to persist among HIV-negative and HIV-positive men, though persistence was more common among HIV-positive men overall. The results may explain the association between high HR-HPV viral load and HR-HPV transmission.